RADIKALISME KEAGAMAAN DI PESANTREN: ANTARA REALITAS SOSIAL DAN KONSTRUKSI STIGMA - Asy'ari Asy'ari (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Religious radicalism in Islamic boarding schools (pesantren) has remained a contested issue in both academic and public discourse, particularly following several terrorism cases involving individuals with pesantren backgrounds. This study aims to examine the relationship between pesantren and religious radicalism by distinguishing empirical social realities from socially constructed stigma. The research employs a qualitative approach using descriptive-analytical methods based on an extensive literature review of scholarly books, journal articles, government reports, and relevant previous studies. The analysis draws upon the sociology of religion, social construction theory, and stigma theory to explain how public perceptions of pesantren are formed and to identify the factors contributing to radicalization. The findings indicate that the relationship between pesantren and religious radicalism is neither causal nor homogeneous. Radicalization emerges from the interaction of multiple factors, including religious leadership, hidden curricula, social networks, political dynamics, transnational ideological influences, and socio-economic conditions. At the same time, the majority of Indonesian pesantren function as institutions that promote Islamic moderation by internalizing the values of tasamuh (tolerance), tawazun (balance), i'tidal (justice), and tawassuth (moderation). The widespread perception linking pesantren to radicalism is largely the result of labeling and overgeneralization based on isolated cases rather than comprehensive empirical evidence. Therefore, efforts to prevent religious radicalism should be grounded in empirical research, strengthened through religious moderation initiatives, and supported by collaborative engagement among government institutions, academics, and pesantren to prevent the reinforcement of misleading stereotypes.